Sodium channels and nociception : the effects of local anesthetics - Drenjančević, Ines; Haršanji-Drenjančević, Ivana; Ivić, Dubravka; Šakić Zdravčević, Kata (2009)
Pain is an unpleasant warning sensation of imminent damage of the tissue or organ, and is a very frequent reason for patients to seek the physician's help. The aim of this paper is to give an overview on the role of voltage gated sodium channels in nociception and to highlight the mechanisms of the action of local anesthetics in inhibiting conduction of ion currents, thus affecting the sense of pain. However, currently available drugs are not considered selective enough and have relatively narrow therapeutic windows, which can limit their usefulness.
Bibliografija: 32 jed.
Keywords: Trauma -- Ozljede -- Opekline -- Lijek -- Stres